How Far Religiosity, Compensation, and Organizational Commitment Impact Toward Employee Performance at Waroeng Steak and Shake, Special Region of Yogyakarta. - Moh. Hishni Alfi Makarim; Andriyastuti Suratman (Cita Konsultindo Research Center, 2024)
This research aims to determine the influences of religiosity, compensation and organizational commitment on employee performance through job satisfaction as an intervening variable at restaurants that have strong religion affiliation. The respondents as 165 respondents were taken from census. Hypothesis testing used in this research uses the Structural Equation Modeling analysis tool with the help of the program version v.3.2.9. This analytical tool is used with the aim of testing the relationships between variables hypothesized in this research. The results indicate that there is an influence of religiosity, compensation and organizational commitment on employee performance. Other results in this research also show that job satisfaction can mediate the influence of compensation and organizational commitment on employee performance.